Benchmarking nurse outcomes in Australian Magnet® hospitals: cross-sectional survey - L. Stone; M. Arneil; L. Coventry; V. Casey; S. Moss; A. Cavadino; B. Laing; AL McCarthy (BMC, 2019)
Abstract Background Positive reports of nursing-related outcomes such as quality nursing care, nursing engagement with work and good practice environment are crucial in attaining and maintaining Magnet® designation. The majority of Magnet®-designated organisations (N = 482) are in the USA, with their aggregate nursing outcomes widely published as benchmark data. Australian Magnet® outcomes have not been aggregated or published to date. Methods The aims are to benchmark educational preparation, occupational burnout, job satisfaction, intention to leave and working environment of nurses in Australian Magnet®-designated facilities and to determine the reliability of the Practice Environment Scale-Australia. The design is a cross-sectional multisite survey set in all three Australian Magnet®-designated organisations. The demographics included age, gender, level of education, years in practice, level of seniority and position title. Two items measured job satisfaction and intent to stay in current employment. The Maslach Burnout Inventory explored the three domains of nursing engagement: depersonalisation, personal achievement and emotional exhaustion. The Australian version of the Practice Environment Scale interrogated participants' perceptions of their work environments. Results 2004 nurses participated (response rate 45.9%). Respondents' mean age was 39.2 years (range 20-72). They were predominantly female and had worked in their current facility for more than 5 years. Eighty five percent had a minimum of a Bachelor's degree. Eighty-six percent of respondents were satisfied or very satisfied with their current position. Eighty eight percent had no intention of leaving their current employer within the next 12 months. Participants rated their hospitals highly in all domains of the practice environment. Respondents reported less burnout in the personal accomplishment and depersonalisation domains than in the emotional exhaustion domain, in which they reported average levels of burnout. The internal consistency of the Practice Environment Scale-Australia was confirmed in this sample (Cronbach α's 0.87-0.9 for subscales and 0.89 for composite score). Conclusion In this paper, we present nursing outcome data from all Australian Magnet® hospitals for the first time. This provides a benchmark that facilitates comparison with nursing outcomes published by Australian non-Magnet® hospitals and with international Magnet® organisations.